Income Inequality in Latin America and the Caribbean: Evidence from Household Surveys - Leonardo Gasparini (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2003)
This paper reports information on income inequality in Latin America and the Caribbean computed from a sample of more than 50 household surveys from 20 LAC countries from 1989 to 2001. Although the core of the statistics is on household income inequality, we also report results on aggregate welfare and polarization. Inequality has moderately increased in South America in the last decade. The two main exceptions are Argentina, with a very large inequality increase, and Brazil, where inequality actually decreased. Changes have not been significant in Central America and the Caribbean. Aggregate welfare has increased in most countries fueled by economic growth and despite unequalizing distributional changes.
Keywords: D3; D63; I2; I31; J11; J21; J31; J82; N36; 330; inequality; distribution; income; wages; education; Latin America; Caribbean.